IMPLEMENTASI METODE AL-QOSIMI DALAM HAFALAN AL-QUR'AN: STUDI KASUS DI MIS IT NURUL IMAN - Arifia, Deanika; Prahastiwi, Eka Danik (LPPM STAI Muhammadiyah Probolinggo, 2024)
The Qur'an, as the holy book of Islam, holds immeasurable value as the primary guide in both spiritual and worldly life. The importance of memorizing the Qur'an as a spiritual practice for Muslims has been a integral tradition in Islam since the time of Prophet Muhammad SAW. The Al-Qosimi method has proven to be one of the effective approaches in enhancing the efficiency of Qur'an memorization. This study aims to evaluate the implementation of the Al-Qosimi method in the process of Qur'an memorization at MIS IT Nurul Iman. In this research, a quantitative phenomenological method is employed, utilizing interviews, observations, and documentation as data collection techniques. The results of the study indicate that the Al-Qosimi method plays a significant role in improving the effectiveness of Qur'an memorization for students at MIS IT Nurul Iman. However, challenges faced include the lack of understanding and mastery of the Al-Qosimi method among teachers. Nonetheless, further training efforts have been undertaken to address this issue. The positive impact of implementing this method is evident from the good achievements in Qur'an memorization by fourth-grade students, where the majority of them have successfully memorized Juz 30. Therefore, the Al-Qosimi method can serve as an effective guideline in Qur'an memorization and can have a positive impact on the formation of students' character and spirituality.